The flock-to-flock force of infection for scrapie in Britain. - Gravenor, M; Cox, DR; Hoinville, L; Hoek, A; Mclean, A (2001)
A postal survey of British sheep farmers provided information on the proportion of farms that experienced their first case of scrapie in each year between 1962 and 1998. We found no evidence of a large increase in the proportion of scrapie-affected farms prior to, during or following the epidemic of BSE in British cattle. After correcting for between-farm heterogeneity in the probability of acquiring scrapie, we estimated the yearly between-flock force of infection since 1962. The current force of infection is estimated at approximately 0.0045 per farm per year and combined with a simple model of scrapie spread provides an estimate of the average duration of a scrapie outbreak on an individual farm. Considering all farms, the average outbreak lasts for five years, but if only those farms that have cases in animals born on the farm are considered, it lasts 15 years. We use these parameter estimates to compare the proportion of farms with scrapie in time periods of different lengths. In the survey, 2.7% of farms had a case in 1998. The 5.3% of farms reporting having a case between 1993 and 1997 is consistent with the hypothesis that the scrapie force of infection remained constant over this period.